ANALISIS PENYERAPAN ISTILAH BOTANI DALAM KAMUS BESAR BAHASA INDONESIA (KBBI) - Muhammad Haris Fadillah Situmorang; Vanny .T. Sitorus; Hana E.P.F Siregar; Nisa Armalia; Nurul Azizah (STKIP Subang, 2026)
Botany is a scientific field with a rich vocabulary largely borrowed from foreign languages, particularly Latin, English, and Dutch. The fifth edition of KBBI, as the normative reference for Indonesian, has incorporated botanical terms through linguistic adaptation processes in accordance with prevailing standardization principles. This study aims to identify and analyze patterns of botanical term borrowing in the fifth edition of KBBI across phonological, orthographic, morphological, and semantic dimensions. A library research method was employed, examining KBBI fifth edition, the General Guidelines for Term Formation (PUPI), and relevant linguistic and botanical references. Data were collected by inventorying entries labeled Bot. in KBBI and analyzed descriptively using a comparative linguistic approach. Findings indicate that phonological and orthographic adaptation dominate the borrowing process, with Latin as the primary source language. Spelling inconsistencies were also identified, highlighting the need for updated scientific term standardization guidelines. This study is expected to contribute to Indonesian scientific lexicography and the strengthening of standardized scientific vocabulary.